Practical measures to ensure sanitary and epidemiological welfare of the population of the Republic of Khakassia - O. V. Ivanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Three emergencies that occurred on the territory of the Republic of Khakassia, their potential influence on sanitary and epidemiological welfare of the population (using water factor as an example) were investigated. We used methods of data collection, analysis and further quality evaluation of fresh water. The results of 2956 analyses of fresh water from centralized sources of drinking water supply and water distribution network of the damaged areas were processed. It was determined that the most substantial deterioration of fresh water quality according to microbiological indicators was recorded in the flood period and upon the liquidation of the consequences of mass fire.